Analisis Kualitas Layanan E-Government dengan Pendekatan E-GovQual Modifikasi - Septa, Frandika; Yudhana, Anton; Fadlil, Abdul (Universitas Diponegoro, 2019)
E-Government Quality (E-GovQual) is a method for measuring the quality of electronic-based information systems in providing services to the public. The Modified E-GovQual Approach uses the overall assessment of the SIMSARPRAS website (Infrastructure Management Information System) based on the user's perception of the SIMSARPRAS website, so that the analysis of service quality becomes more accurate and precise in its assessment. Overall assessment of the E-GovQual Modification approach aims to determine the quality of service based on the level of influence of the 6 independent variables of E-GovQual, namely the ease of use, trust variable, function variable and form interaction (functionality of the interaction environment), variable reliability (reliability), variable content and display information (content and appearance of information) and supporting variables (citizen support) to the dependent variable, namely user satisfaction. This study uses the modified E-GovQual method by conducting validity, reliability testing, multiple linear regression analysis, t test and F test on the results of the questionnaire on 500 respondents, with 6 independent variables and 1 dependent variable. The results obtained in this study note that the quality of SIMSARPRAS website services has an effect of 61.7% on user satisfaction, and the correlation coefficient value is 78.5%. With these results, it was concluded that the SIMSARPRAS website has good service quality as an application that performs public services, and there is a strong relationship between the quality of E-Government services and the satisfaction of E-Government users. The results of this study also become a reference or evaluation material to the Ministry of Religion as the owner of the SIMSARPRAS website and can also be used as a reference for similar research.